The Role of Halimbubu Foundation in Promoting Ta’awun among Youth - Sofya Ayu; Basri Basri; Madi Madi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the role of the Halimbubu Foundation in promoting ta’awun, defined as mutual help and cooperation rooted in Islamic values, among youth in the context of modernization. A qualitative approach was employed, with data collected through interviews involving youth members and administrators of the Halimbubu Foundation in Baubau City. The findings show that the foundation plays a significant role in fostering social awareness, mutual assistance, and cooperative attitudes through religious and social activities. However, modern lifestyle tend to reduce direct social interaction among youth. Despite this challenge, continuous guidance and structured programs have strengthened the implemention of ta’awun values. This study concludes that the Halimbubu Foundation contributes positively to the development of youth moral values amid modernization.